[Ulotka. Incipit] Festlied dem Club zum November 1879 gewidmet. (Danzig : [wydawca nieznany], 1879)
Ulotka z tekstem pieśni.
Keywords: Gdańsk (Polska) -- 19 w. -- druki ulotne; Druki ulotne -- 19 w; Druki ulotne; Pieśni niemieckie -- teksty